A Measurement Approach to Knowledge Management (2019)
This exploratory study has been directed to establish how knowledge management has been used to generate added value in organizations in Bogota. In order to accomplish this, a questionnaire was used in a sample of 1.168 executives and workers in 48 organizations, which had different sizes and belonged to different industrial sectors. The members of the survey group coincidentally identified knowledge management as a strategy to generate value and to strengthen the competitive advantages in the organizations. However, this positive perception is noticed mainly in factors related to organizational culture and memory rather than in factors related to internal organizational capacities. The obtained results were obtained from the application of two research tools, the knowledge management questionnaire and the IMIO Matrix.